Psychological Weaning Among Kindergarten Children from The Perspective of Teachers (Raparin Journal of Humanities (RJH), 2026)
The purpose of the present research was to examine the level of psychological weaning among kindergarten children as perceived by their teachers, taking into account the differences in age, gender, birth order, and parental literacy levels. The study utilized a descriptive research design since it was deemed the best to fit the study’s objectives. The research population consisted of kindergarten teachers throughout the Sulaymaniyah city, during the 2024-2025 academic year (N = 1,321), from whom a sample of 439 teachers was taken. A 40-item consultation form was designed for the data collection which manipulated previous field studies. To ensure its validity, the instrument was verified in advance by administering it to the sample. Arithmetic mean, standard deviation, Pearson correlation coefficient, t-test, and one-way ANOVA were the primary statistical techniques used in the study. The findings revealed that children experience a high level of psychological weaning. Particularly, substantial differences were discovered depending on gender, with female children experiencing higher levels of psychological weaning. While there were no major differences in terms of age (4-5 years), birth order, or parental literacy levels.